Increasing Vocabulary Through Translation Of Indonesian Short Story Into English (A Case Study At Sman 1 Watampone)Increasing Vocabulary Through Translation Of Indonesian Short Story Into English (A Case Study At Sman 1 Watampone) - Zulkhaeriyah Zulkhaeriyah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2017)
The objective of the research is to find out whether or not translating of Indonesian short story into English is able to improve students’ vocabulary.The writer employed experimental method, which applied one group pre-test, treatment, and post-test design. The sample consists of 20 students taken from the second year students of SMAN 1 Watampone. The writer collected data by using translating of Indonesian short story into English.The result of the data shows that there are significant difference between pre-test and post-test. The value of post-test (76.25) is greater than in the pre-test (38.04) which the standard deviation of pre-test is (15.32) and in the post-test is (11.44) which mean that the hypothesis is accepted. Based upon the findings and discussion, the researcher concludes that the translation of Indonesian short story into English is effective to increase the students’ vocabulary.